FEDERALNE PRAWO ŁASKI W STANACH ZJEDNOCZONYCH AMERYKI - Wojciech Kwiatkowski (Zeszyty Prawnicze)
United States Federal Executive Clemency Summary The article relates to the core principles underlying federal executive clemency as an act that mitigates the punitive consequences resulting from a criminal conviction. Presidential clemency is also the least appreciated and most misunderstood of presidential powers – the Constitution places no limits on the way the President exercises his power to pardon, except in cases of impeachment. The article gives a historical overview of the power of clemency in the U.S. Constitution. It also examines the evolution of the Supreme Court’s views on clemency over the years, both substantively and procedurally, and how the Court has interpreted the power to grant pardons, conditional pardons, as well as amnesties, commutations of sentence, remissions of fines and forfeitures, and respites. It discusses the procedure for clemency, including the role of the Pardon Attorney, and concludes with a proposal of certain reforms to reinvigorate the federal pardon process and restore its moral force.